Upaya Meningkatkan Kompetensi Guru dalam Menyusun Silabus melalui Bimbingan dan Supervisi di SD Negeri 1 Kalinanas - S Rusmiyati (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2018)
Abstract. The purpose of this study is to improve the competence of teachers in SDNegeri 1 Kalinanas in compiling learning syllabus documents. The study was conducted at SD Negeri 1 Kalinanas for ± 5 months starting July 2015 to December 2015. The number of teachers in SD Negeri 1 Kalinanas who attended Guidance and Supervision amounted to 9 teachers. Data collection is done through interviews, observation and documentation. From the interview, the results showed that overall the teachers at SD Negeri 1 Kalinanas stated that it was important to prepare the learning syllabus documents very well. The study was conducted in 2 cycles. In the pre cycle, the average value of 77 was obtained with a percentage of 52% achievement of all teachers in the syllabus preparation research indicator. In cycle 1 the average value was 84 with 67% achievement of all teachers in the syllabus preparation research indicators, and the second cycle on average 98 with a 95% percentage of achievement of all teachers in the syllabus preparation research indicators. There was an increase in teacher competency in the preparation of syllabus after Guidance and Supervision were carried out by the principal of SD 1 Kalinanas.